2023
DOI: 10.3390/app13063812
|View full text |Cite
|
Sign up to set email alerts
|

Fish Detection and Classification for Automatic Sorting System with an Optimized YOLO Algorithm

Abstract: Automatic fish recognition using deep learning and computer or machine vision is a key part of making the fish industry more productive through automation. An automatic sorting system will help to tackle the challenges of increasing food demand and the threat of food scarcity in the future due to the continuing growth of the world population and the impact of global warming and climate change. As far as the authors know, there has been no published work so far to detect and classify moving fish for the fish cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The object detection approach is categorized into two methods: the two-stage and one-stage method. The two-stage approach based on old research gives high prediction accuracy but cannot achieve speed and higher performance [5]. The two-stage category networks to detect objects are Region-Based Convolutional Neural Network (R-CNN), Fast R-CNN, Faster R-CNN, and Spatial Pyramid Pooling Network (SPP-net) [23].…”
Section: Research Study Of Vehicle Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The object detection approach is categorized into two methods: the two-stage and one-stage method. The two-stage approach based on old research gives high prediction accuracy but cannot achieve speed and higher performance [5]. The two-stage category networks to detect objects are Region-Based Convolutional Neural Network (R-CNN), Fast R-CNN, Faster R-CNN, and Spatial Pyramid Pooling Network (SPP-net) [23].…”
Section: Research Study Of Vehicle Detectionmentioning
confidence: 99%
“…Various object detection algorithms have been proposed based on the one-stage approach. They are fast and make predictions of objects with high efficiency [5]. Joseph Redmon et al [29] proposed a YOLO model in 2016 that is state-of-the-art in real-time object detection.…”
Section: Research Study Of Vehicle Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large amounts of collected data require automated processing to efficiently extract the task-specific information. Several studies [11,18,19,12,9,10,20] demonstrated the application D R A F T -w o r k i n p r o g r e s s of well-established deep neural networks, such as Single Shot MultiBox Detector [11], Region-Based Convolutional Neural Networks [18,19], and most of them used methods from the YOLO-family approaches [12,9,10,20,19,13,19,21,14]. In contrast, there are few studies dealing with fish detection along with weight estimation.…”
Section: Introductionmentioning
confidence: 99%